When did the stock market start to react less to downgrades by Moody's, S&P and Fitch? - Ginevra Marandola; Rossella Mossucca (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
This paper studies the stock market response to corporate downgrades by S&P, Moody's and Fitch between 1999 and 2011. The empirical evidence shows that cumulative abnormal returns around downgrades become significantly smaller (in absolute value) after the release in 2003 of the Securities and Exchange Commission's Report on credit rating agencies. The Report addresses concerns related to the agencies and marks a turning point in the attitude of U.S. regulators towards a more critical approach. This has a strong impact on investors that respond by reacting less to downgrades.
Keywords: G14; G24; G28; 330